2019
DOI: 10.1038/s42005-019-0196-7
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic observation of efficient charge transport processes across domain boundaries in donor-acceptor-type conjugated polymers

Abstract: Backbone rigidity of conjugated polymers is suggested to play an essential role in realizing high-mobility transistors through the efficient interconnection of crystalline domains by tie molecules as discussed for the recently-developed donor-acceptor (DA)-type copolymers. However, no studies have directly observed interdomain hopping in these DA copolymers. Here, highly-efficient interdomain charge transport is observed in two typical high-mobility DA copolymers from the microscopic observation of charge carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 66 publications
4
23
1
Order By: Relevance
“…S5. The planar molecules enable highly efficient interdomain connection (40)(41)(42)(43)(44), which may explain the metallic transition observed in the present study. However, the domain connection by tie molecules should be quite sensitive to the doping condition, presumably due to the structural/energetic disorder of the isolated tie molecules induced by the dopant.…”
supporting
confidence: 57%
“…S5. The planar molecules enable highly efficient interdomain connection (40)(41)(42)(43)(44), which may explain the metallic transition observed in the present study. However, the domain connection by tie molecules should be quite sensitive to the doping condition, presumably due to the structural/energetic disorder of the isolated tie molecules induced by the dopant.…”
supporting
confidence: 57%
“…An Arrhenius plot (Figure 3c) indicated that conductivity in the OSC is thermally activated and follows an Arrhenius relationship. Here, an E a of 82 ± 8 meV was calculated which is comparable to that calculated by Tanaka et al [32] from field-induced electron spin resonance (ESR) spectroscopy measurements, of 68 meV.…”
Section: Response To Analyte Vapourssupporting
confidence: 86%
“…[ 31a,60 ] In such cases, tie chains have the potential to reduce interaggregate transport barriers to intraaggregate limits. [ 61 ] Moreover, the mixed “face‐on” and “edge‐on” morphology is further expected to benefit transport in TGBC OFETs as well. [ 62 ]…”
Section: Resultsmentioning
confidence: 99%